[1,2] -Connected domination number of graphs - et. al., G. Mahadevan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A set in a graph G is said to be a -connected dominating set if for every vertex , and is connected. The minimum cardinality of a -connected dominating set is called the -connected domination number and is denoted by . In this paper, we initiate a study of this parameter.